Penerapan Metode System Usability Scale dalam Pengujian Rancangan Mobile Apps Gamification Tari Rakyat di Indonesia - Arief Rais Bahtiar; Muhamad Azrino Gustalika (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Indonesia has many dances in each region. Traditional dance and folk dance are dances that existed in Indonesia before the development of contemporary dance. As one of the local cultures in each area, dance art is included in local content at the elementary to high school level. The changing curriculum has disrupted local cultural education in the world of education some time ago. In addition to these factors, the lack of interactive learning media at least affects. The purpose of this study is to develop a learning pattern for folk dance as a local culture in Indonesia through an interactive mobile application. In addition, this research is used to help preserve and introduce the folk dance arts of each region to students in Indonesia. Gamification can be an alternative for developing folk dance learning. What usually happens is the lack of innovation in conventional learning media to attract students' interest in studying local culture, especially folk dance as a local content subject. This activity is a folk dance education about history, regional origins and dance movements. The result of this application is a folk dance game in Indonesia. There are several levels that must be passed to be able to complete this game. Each season will be taken 3 people who get the reward. The rewards that we design are based on the prizes preferred by elementary, junior high and high school students. Based on the results of the System Usability Scale evaluation, the prototype designed got a score of 86.25% and was considered to have met the usability element.